Chronic Pain in Inflammatory Arthritis: Mechanisms, Metrology, and Emerging Targets—A Focus on the JAK-STAT Pathway - Fausto Salaffi; Giovanni Giacobazzi; Marco Di Carlo (Pain Research and Management)
Chronic pain is nowadays considered not only the mainstay symptom of rheumatic diseases but also “a disease itself.” Pain is a multidimensional phenomenon, and in inflammatory arthritis, it derives from multiple mechanisms, involving both synovitis (release of a great number of cytokines) and peripheral and central pain-processing mechanisms (sensitization). In the last years, the JAK-STAT pathway has been recognized as a pivotal component both in the inflammatory process and in pain amplification in the central nervous system. This paper provides a summary on pain in inflammatory arthritis, from pathogenesis to clinimetric instruments and treatment, with a focus on the JAK-STAT pathway.